Delayed Presentation of Isolated Jejunal Perforation Following Accidental Trauma - KSHITIJ ARUN MANERIKAR; PRIYANK VERMA; ABHIJIT GHATAGE; SHISHIR GARG; MIRAT DHOLAKIA (Journal of Clinical and Diagnostic Research, 2017)
Blunt abdominal trauma can injure any abdominal organs which had significant morbidity and mortality in paediatric age group. It can lead to duodenal, jejunal or rather any bowel perforation. Isolated jejunal perforation still remains rare entity with less documented reports in specifically paediatric age group. We hereby present a case of three-year-old female child with isolated jejunal perforation, post history of fall from height. Early exploration and prompt surgical intervention led to successful outcome in this patient.